(untitled) (Terr@ Plural, 2020)
The region of water level fluctuation in reservoirs represents a disturbance zone that experiences exposure to cyclical flooding, due to its operations, inducing marginal mass movements that mix with the constant transport of sediments from adjacent hydrographic basins. The objective of this study is to determine the best source of multispectral images of medium spatial resolution to diagnose hydrodynamic processes, proposing a classification key based on the composition of satellite image bands. In addition, understand what the main types of mass movements occur and how natural and anthropic factors influence these events. For this, we qualitatively compare images from the Landsat-5 TM, Landsat 8 OLI, and Sentinel-2 MSI satellites, in combinations of simple bands and based on equation with detailed images obtained by remotely piloted aircraft. We found that the association between the simple composition true color 432 together with the composition VRE-VIS, adapted in this study, provides enhancements for transporting active sediments on exposed soil at the reservoir margins and the combination VNIR-VRE2, also adapted, presents better clarity in relation to the depth of the water depth.